A proposed strategy for anticoagulation therapy in noncompaction cardiomyopathy. (16th December 2021) - Chimenti, Cristina; Lavalle, Carlo; Magnocavallo, Michele; Alfarano, Maria; Mariani, Marco Valerio; Bernardini, Federico; Della Rocca, Domenico Giovanni; Galardo, Gioacchino; Severino, Paolo; Di Lullo, Luca; Miraldi, Fabio; Fedele, Francesco; et al.
Abstract: Noncompaction cardiomyopathy (NCCM) is a rare condition characterized by prominent trabeculae, deep intertrabecular recesses, and a left ventricular myocardium with a two‐layered structure, characterized by a spongy endocardial layer and a thinner and compacted epicardial one. NCCM can be isolated or associated with other congenital heart diseases and complex syndromes involving neuromuscular disorders and facial dysmorphisms. To date, more than 40 genes coding for sarcomeric, cytoskeletal, ion channels, and desmosomal proteins have been identified. Clinical presentation is also highly variable, ranging from no symptoms to end‐stage heart failure (HF), lethal arrhythmias, sudden cardiac death, or thromboembolic events. In particular, the prevalence of thromboembolism in NCCM patients appears to be higher than that of a similar, age‐matched population without NCCM. Thromboembolism has a multifactorial aetiology, which is linked to genetic, as well as traditional cardiovascular risk factors. In previous studies, atrial fibrillation (AF) was observed in approximately 25–30% of adult NCCM patients and embolism had a cardiac source in ~63–69% of cases; therefore, AF represents a strong predictor of adverse events, especially if associated to HF and neuromuscular disorders. Left ventricular dysfunction is another risk factor for thromboembolism, as a result of blood stagnation and local myocardial injury. Moreover, it is not completely clarified if the presence of deep intertrabecular recesses causing stagnant blood flow can constitute per se a thrombogenic substrate even in absence of ventricular dysfunction. For the clinical management of NCCM patients, an appropriate stratification of the thromboembolic risk is of utmost importance for a timely initiation of anticoagulant therapy. The aim of the present study is to review the available literature on NCCM with particular attention on thromboembolic risk stratification and prevention and the current evidence for oral anticoagulation therapy. The use of direct oral anticoagulants vs. vitamin K antagonists is also discussed with important implications for patient treatment and prognosis.